Publication manual of the American psychological Association - [Tidak Terdaftar] ([Tidak Terdaftar], 2001)
The "Publication Manual" is the style manual of choice for writers, editors, students, and educators. Although it is specifically designed to help writers in the behavioral sciences and social sciences, anyone who writes non-fiction prose can benefit from its guidance. The newly-revised Sixth Edition has not only been rewritten. It has also been thoroughly rethought and reorganized, making it the most user-friendly "Publication Manual" the APA has ever produced. You will be able to find answers to your questions faster than ever before. When you need advice on how to present information, including text, data, and graphics, for publication in any type of format--such as college and university papers, professional journals, presentations for colleagues, and online publication--you will find the advice you're looking for in the "Publication Manual."